The 'High Achievers' project: an assessment of the support for students with autism attending UK universities. Issue 6 (18th August 2018) - Chown, Nick; Baker-Rogers, Joanna; Hughes, Liz; Cossburn, Kleio Nicola; Byrne, Pam
Abstract: In the UK autism is classed as a disability under the Disability Discrimination Act 2005. Under the Special Educational Needs and Disability Act 2001, higher education institutions in the UK are legally required to make reasonable adjustments for students with disabilities who are placed at a substantial disadvantage in comparison to students without disabilities. Despite the social difficulties associated with autism, and autistic students being at a heightened risk of dropping out of university, high-functioning autistic students are often high achievers academically. The National Audit Office recognises university as a desirable option for academically gifted students with autism. As there have been few studies directly examining the needs of autistic students in post-secondary education by established researchers, we undertook an online questionnaire survey of all UK universities, other than those under foreign ownership, to ascertain current levels of support for students with autism in higher education. This was followed up with Freedom of Information Act requests to establishments that did not respond to the survey. We report our findings based on responses from 99 universities out of approximately 160 establishments in total. As autistic university graduates are at a disadvantage when compared to their non-autistic peers in obtaining employment after graduation, we propose that all higher education establishments follow the government recommendation for providers of services not covered by the Autism Act 2009, but who support people into employment, to adopt the Statutory Guidance issued in connection with the Adult Autism Strategy. Universities should consider seeking accreditation under the National Autistic Society's accreditation scheme.